The Relationship Between Fat Intake and Physical Activity and Nutritional Status in Students of SMPN 22 Surakarta - Istianah Nur Adila; Nur Lathifah Mardiyati; Dwi Sarbini (Jurnal Impresi Indonesia, 2025)
Adolescents are an age group that is vulnerable to nutritional problems due to physiological changes and modern lifestyles. This study aims to determine the relationship between fat intake and physical activity and nutritional status in SMPN 22 Surakarta students. This study uses an analytical observational design with a cross-sectional approach. The sample amounted to 141 students who were selected using a simple random sampling technique. Fat intake data was collected through the 24-Hour Food Recall method for three non-consecutive days and analyzed using Nutrisurvey 2007, while physical activity was measured using the PAQ-A questionnaire. Nutritional status is determined based on the body mass index by age (BMI/U) based on z-score using WHO standards. The results of statistical analysis showed that there was no relationship between fat intake and nutritional status (p = 0.997) or between physical activity and nutritional status (p = 0.070) in SMPN 22 Surakarta students. This study indicates that other factors beyond fat intake and physical activity may play a role in determining adolescent nutritional status.